Pengaruh Pengungkapan Laporan Sustainabilitas Terhadap Kinerja Keuangan pada Perusahaan Sektor Energi Pertambangan yang Terdaftar di Bursa Efek Indonesia - Intan Purnama Putri; Nurhafifah Amalina (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to test and analyze the effect of disclosure of sustainability reports consisting of economic dimensions, environmental dimensions, and social dimensions, on company performance. In this study, the population used is mining companies listed on the Indonesia Stock Exchange (IDX) in 2021 - 2024. The type of data used is secondary data, namely data derived from annual reports and sustainability reports. The purposive sampling method used in this study obtained 25 companies with a total analysis of 100 samples in mining companies. This study uses the Feasible Generalized Least Square (FGLS) approach with panel data regression analysis techniques. The results showed that the partial test on the disclosure of sustainability reports in the environmental dimension had a significant effect on ROA, but the other two dimensions, namely the economic and social dimensions, did not have a significant effect on ROA. These results are expected to be a reference for companies, especially the mining sector in Indonesia, to be able to optimize the disclosure of sustainability reports which have proven to be an important component in driving company profitability.